2018
DOI: 10.1038/s41467-018-03366-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of an agarose metabolic pathway acquired by a human intestinal symbiont

Abstract: In red algae, the most abundant principal cell wall polysaccharides are mixed galactan agars, of which agarose is a common component. While bioconversion of agarose is predominantly catalyzed by bacteria that live in the oceans, agarases have been discovered in microorganisms that inhabit diverse terrestrial ecosystems, including human intestines. Here we comprehensively define the structure–function relationship of the agarolytic pathway from the human intestinal bacterium Bacteroides uniformis (Bu) NP1. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 79 publications
4
75
1
Order By: Relevance
“…Results of Pred-Lipo, Signal P, and Lipo P analyses indicated that Ce383 could be cytoplasmic whereas Ce362 might be anchored in the membrane. The predicted intracellular localization supports the hypothesis that Ce362 and/or Ce383 might be the missing 3,6-anhydro-D-galactosidase, as neocarrabiose is believed to be transported into the periplasm or cytoplasm in analogy with neoagarobiose (38,39). However, functional analysis was not possible because expression of both genes in E. coli failed to give soluble, active enzymes.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Results of Pred-Lipo, Signal P, and Lipo P analyses indicated that Ce383 could be cytoplasmic whereas Ce362 might be anchored in the membrane. The predicted intracellular localization supports the hypothesis that Ce362 and/or Ce383 might be the missing 3,6-anhydro-D-galactosidase, as neocarrabiose is believed to be transported into the periplasm or cytoplasm in analogy with neoagarobiose (38,39). However, functional analysis was not possible because expression of both genes in E. coli failed to give soluble, active enzymes.…”
Section: Resultssupporting
confidence: 63%
“…The supernatants were dried in a speed-vacuum centrifuge. Samples were labeled with 2 l 8-aminonaphthalene-1,3,6-trisulfonate (ANTS) solution (0.15 M ANTS dissolved in acetic acid-water [3:17 {vol/vol}]) and with 5 l freshly prepared 1 M sodium cyanoborohydride-dimethyl sulfoxide (DMSO) (38). After incubation overnight at 37°C, 25 l glycerol (25%) was added and 5 to 10 l was loaded onto a 6% stacking and 27% running polyacrylamide gel.…”
Section: Methodsmentioning
confidence: 99%
“…This observation could be explained by geographic bias in the humans from which they were cultured or latent populations of bacteria that are enriched only after seaweed consumption. As an additional approach to identify bacteria that possess these traits, we surveyed stool samples from 240 different healthy volunteers using an enrichment strategy (see Methods ) that was previously successful in isolating an agarose-degrading strain of B. uniformis 3,5 . Using this approach, we isolated 33 new strains that were enriched based on the ability to grow on CGN, porphyran or agarose ( Extended Data 3 ).…”
Section: Enrichment Culture To Isolate New Seaweed Degrading Strainsmentioning
confidence: 99%
“…As with nearly all dietary fibers, humans lack these enzymes and therefore rely on colonic bacteria for the ability to digest them. Previous studies have documented a few examples in which symbiotic bacteria belonging to Bacteroides— a dominant genus in humans—possess genes for degrading seaweed-derived porphyran 3,4 , agarose 5 , alginate 6,7 and laminarin 8 . In the first three cases, the genes involved often have closest homologs in marine Bacteroidetes, which are physiologically different from gut Bacteroides but share similar mechanisms for polysaccharide degradation 9 .…”
mentioning
confidence: 99%
“…In this special issue, Cornish et al (2019) provided a mini-review on the microbial continuum, which promotes the judicious consumption of a varied diet of macroalgae and the benefi ts for human health and nutrition (Gentile and Weir, 2018;Mathieu et al, 2018;Pluvinage et al, 2018). Zhang et al (2019a) analyzed the structures and anti-complement activity of polysaccharides extracted from Grateloupia livida , and provided evidence that the molecular weight and sulfate content were important factors contributing to biological activity.…”
mentioning
confidence: 99%